An otolaryngologist and an opera singer: the peculiar friendship between Doctor Marano and Enrico Caruso. (3rd December 2021) - Mion, Marta; Barillari, Umberto; Barillari, Maria R.; Martini, Alessandro
Abstract: Purpose: Enrico Caruso was one of the most famous Italian opera singer who lived between the XIX th and the XX th century. Material and methods: On the occasion of the centenary of his death, we propose some mails that documented the correspondence between the tenor and Salvatore Marano, his otolaryngologist and dear friend. Conclusions: Reading the correspondence between them, we can appreciate an inedited side of the famous singer.